How did individuals on Instagram discuss COVID-19 in the month following official pandemic status? A examination of user content. Issue 2 (3rd April 2021) - Meleo-Erwin, Zoë C.; Basch, Corey H.; Fera, Joseph; Arrowood, Matthew
Abstract: Objectives: Instagram is a popular social media site used by high numbers of young people. This study was designed to investigate COVID-19 content on Instagram during the month following official pandemic status from the World Health Organization (WHO). Methods: A total of 200 posts were collected and analyzed over a four-week period between mid-February and mid-March 2020. Results: The vast majority of posts did not address recommended prevention measures. Further, only approximately one-third of the posts referenced a reputable source. Finally, the nature of posts changed over time was impacted by type of poster and reflected a tone of anxiety. Conclusions: The findings underscore the urgent need for public health officials to be aware of and address social media content on novel health threats. Furthermore, it is imperative that communicating risk on social media, such as Instagram be geared to young people. Failure to do so may hinder prevention, mitigation, and suppression strategies.